2008
DOI: 10.3852/07-042r1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity assessment of arctic and borealAgaricustaxa

Abstract: We provide a phylogenetic diversity assessment study in genus Agaricus as part of our ongoing work to saturate ITS and LSU rDNA sequence diversity of soil-dwelling fungi in Alaska. Pairwise sequence similarity-based groupings and statistical parsimony analyses were applied to delimit operational taxonomic unit (OTU) and were compared to results of full phylogenetic analyses. Our results show that the proportion of section Arvenses taxa is particularly high in the boreal forest and hypo-arctic (low arctic) regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 49 publications
(44 reference statements)
2
30
0
1
Order By: Relevance
“…OTUs similar to all the soil isolates examined for organic acid secretion and Pb solubilization in this study were also found in all samples in the pyrosequence analysis (at a Ն97% identity cutoff) (20,33). None of our isolates were dominant in these soils; however, they were present at levels greater than 1%, which is not necessarily uncommon for fungi (42,48).…”
Section: Discussionsupporting
confidence: 60%
“…OTUs similar to all the soil isolates examined for organic acid secretion and Pb solubilization in this study were also found in all samples in the pyrosequence analysis (at a Ն97% identity cutoff) (20,33). None of our isolates were dominant in these soils; however, they were present at levels greater than 1%, which is not necessarily uncommon for fungi (42,48).…”
Section: Discussionsupporting
confidence: 60%
“…The resulting PCR libraries were shipped frozen to the Broad Institute, Cambridge Massachusettss (USA), where transformation, plating, colony picking, Templiphi reactions, and sequencing were carried out on automated equipment, using M13 forward and reverse vector primers. These molecular methods have been partially described elsewhere (Taylor et al 2007, Geml et al 2008. Site coordinates and numbers of soil cores and sequences generated are given in Appendix A: Tables A1 and A2.…”
Section: Pcr and Sequencingmentioning
confidence: 99%
“…ITS is also used in some fungi for providing an indication of delimitation by a measure of the genetic distances (26). However, phylogenetic approaches are also being used to identify taxonomic units in environmental sampling of fungi (27) and are often more effective in comparison (28).…”
mentioning
confidence: 99%